Power Quality Enhancement in Grid Connected PV Systems using High Step Up DC-DC Converter - V S Prasadarao K; K V Krishna Rao; P Bala Koteswara Rao; T. Abishai (Institute of Advanced Engineering and Science, 2017)
Renewable energy sources (RES) are gaining more importance in the present scenario due to the depletion of fossil fuels and increasing power demand. Solar energy is the one of the most promising as it is clean and easily available source. The voltage obtained from the PV system is low. This voltage is increased by high step up dc-dc converter which uses only one switch leads to low switching losses and hence the efficiency of this converter is high. To get the good response this converter is operated in closed loop manner. Integration of PV system with existing grid has so many issues like distorted voltage, current and reactive power control etc. This paper presents a four leg inverter which works on hysteresis current control technique to address the power quality issues like reactive power compensation, balanced load currents and compensation of neutral current. The switching to the inverter is designed in such a way that it supplies the extra current to stabilise the current of the grid that is being supplied to the loads. Finally, the proposed technique is validated by using mat lab/Simulink software and corresponding results are presented in this paper.